Resistive switching and voltage induced modulation of tunneling magnetoresistance in nanosized perpendicular organic spin valves - Robert Göckeritz (AIP Advances, 2016)
Nanoscale multifunctional perpendicular organic spin valves have been fabricated. The devices based on an La0.7Sr0.3MnO3/Alq3/Co trilayer show resistive switching of up to 4-5 orders of magnitude and magnetoresistance as high as -70% the latter even changing sign when voltage pulses are applied. This combination of phenomena is typically observed in multiferroic tunnel junctions where it is attributed to magnetoelectric coupling between a ferromagnet and a ferroelectric material. Modeling indicates that here the switching originates from a modification of the La0.7Sr0.3MnO3 surface. This modification influences the tunneling of charge carriers and thus both the electrical resistance and the tunneling magnetoresistance which occurs at pinholes in the organic layer.